An Analysis of Reiteration in Research Paper Writing at The Sixth Semester of Muhammadiyah University of Bengkulu - Nici Jarsi (Teaching English and Language Learning English Journal, 2022)
This research entitled an analysis of reiteration in research paper writing at the sixth semester of Muhammadiyah University of Bengkulu. It analyzes reiteration on student’s research paper using Halliday and Hasan’s theory (1976). The aims of this analysis are: the first is to identify the types of reiteration used in the student’s research paper, the second is to find out the most types of reiteration lexical cohesion found in the research paper. Qualitative method was used in conducting this project. In collecting the data, the reiteration in the research paper were identified and recorded in Microsoft word according to the types of reiteration. In analyzing the data, the types of reiteration in the research paper were analyzed based on the theory of Halliday and Hasan (1976). The results of the analysis showed that four types of repetition that used by students in their research paper, that are repetition, antonymy, synonymy and hyponymy.The most most reiteration was repetition (98,226 %). Meanwhile, the less most reiteration was antonymy (0.669%), synonymy (0,640 %) and hyponymy (0.005 %). From the analysis, it could be concluded that repetition is the most reiteration type used by students at the sixth semester, while hyponymy is the least reiteration type used. The use of reiteration lexical cohesion is important in some aspects of English. It helps the writer and readers to get more understanding of the point in argumentative research. Besides, it also helps readers and writers to solve the problem of new vocabularies. Keywords: analysis, reiteration, writing, qualitative research